Novel Onset of Cutaneous Lupus Erythematosus Induced by Pembrolizumab - Dimitrii Pogorelov; Heribert Strotkötter; Vesna Bjelic-Radisic; Ulrich Wesselmann; Jonas Hübinger; Simona Sabulyte; Silke C. Hofmann; Galina Balakirski (Medical Journals Sweden, 2024)
Abstract is missing (Short Communication)